Studi Literatur: Pelatihan sebagai Sarana Pengembangan Untuk Mendorong Inovasi Guru dalam Menyiapkan Pembelajaran yang Bermutu - Narmayani, Narmayani (Universitas Negeri Malang, 2024)
Abstract Training is one of the most important tools to help teachers adopt creative teaching methods and improve teaching quality. This research is a literature study with a descriptive qualitative research type with a literature review that seeks to describe the role of training to encourage teacher innovation in preparing quality learning. In this study, the author used various sources such as articles, journals and documents related to this study. This literature study focuses on training to encourage teacher innovation and its impact on education quality. The purpose of this study is to determine the role of training in developing teachers' innovation skills in designing quality learning. The results of this study show that training is an effective tool to improve teachers' creativity, motivation and ability to design relevant, effective and quality learning. Through effective training strategies, teachers are empowered to design engaging and effective learning environments, which ultimately contribute to improving the quality and relevance of education.